FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BEI - Sutiningsih, Sutiningsih; Pradipta, Arya; Ghazi, Muhammad (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The objective of this study is to obtain empirical evidence of audit committee, leverage, return on assets, company size, sales growth, and institutional ownership as independent variables to tax avoidance as the dependent variable. The company used in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020. The number of research samples obtained using purposive sampling method are 48 sample companies with a total of 192 data. This research uses multiple regression method for data analysis. The result of this study shows the result that audit committee, return on assets, and sales growth have influence to tax avoidance, while leverage, company size, and institutional ownership have no influence to tax avoidance.